Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of five sea cucumber species through PCR-RFLP analysis - Yingchun Lv; Rong Zheng; Tao Zuo; Yuming Wang; Zhaojie Li; Yong Xue; Changhu Xue; Qingjuan Tang (Journal of Ocean University of China, 2014)

Halopenitus salinus sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)